Assessing the Macroeconomic Impact of Structural Reforms The Case of Italy - Lusinyan, Lusine (IMF Working Papers; Working Paper ;, 2013)
Wide-ranging structural reforms are underway in Italy, aimed at addressing key bottlenecks in the product and labor markets. Our analysis, based on the IMF's Global Integrated Monetary and Fiscal model (GIMF), attempts to quantify the potential gains to the economy from a comprehensive package of structural reforms. We find that these gains can be sizeable. While in most cases, the reforms go in the right direction, their impact would depend on effective and timely implementation. In some areas, especially in the labor market, reforms would benefit from further strengthening. The priorities should be to strengthen competition in the non-tradable sector and make the labor market more efficient and inclusive, supported by growth-friendly fiscal reforms.